2015
DOI: 10.3389/fpsyg.2015.00733
|View full text |Cite
|
Sign up to set email alerts
|

The comparability of the universalism value over time and across countries in the European Social Survey: exact vs. approximate measurement invariance

Abstract: Over the last decades, large international datasets such as the European Social Survey (ESS), the European Value Study (EVS) and the World Value Survey (WVS) have been collected to compare value means over multiple time points and across many countries. Yet analyzing comparative survey data requires the fulfillment of specific assumptions, i.e., that these values are comparable over time and across countries. Given the large number of groups that can be compared in repeated cross-national datasets, establishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…Second, there is still a lack of evidence from simulation studies about how small should be the prior variance on differences in factor loadings/intercepts across groups to conclude with certainty that the approximate invariance does hold . The existing results suggest that the prior variance of 0.05 is sufficient to avoid substantial bias in latent mean comparisons (Van de Schoot et al, 2013), and few practical applications of the method, including one in the presented paper, rely on that recommended cut-off value (e.g., Zercher et al, 2015. I tried to impose stricter levels of invariance for each of the six wave-specific models.…”
Section: Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Second, there is still a lack of evidence from simulation studies about how small should be the prior variance on differences in factor loadings/intercepts across groups to conclude with certainty that the approximate invariance does hold . The existing results suggest that the prior variance of 0.05 is sufficient to avoid substantial bias in latent mean comparisons (Van de Schoot et al, 2013), and few practical applications of the method, including one in the presented paper, rely on that recommended cut-off value (e.g., Zercher et al, 2015. I tried to impose stricter levels of invariance for each of the six wave-specific models.…”
Section: Limitationsmentioning
confidence: 98%
“…In addition, one can simply remove the most outlying unit(-s) from the sample or try to establish partial (metric or scalar) approximate invariance by releasing approximate equality constraints for problematic items (that is, loadings and/or intercepts for which the highest countryspecific deviations from the sample average parameter values are observed). 16 I do not apply frequentist MGCFA to the same samples, as it was done [for the purpose of comparison between the two approaches] in similar applications of the Bayesian approximate invariance testing by Davidov et al (2015), Cieciuch et al (2014), and Zercher et al (2015). I have already shown that the classical approach failed to establish scalar invariance of -choice‖ even across ten cultural zones, so it is quite reasonable to anticipate that it will fail at the country level (much more heterogeneous) as well.…”
Section: B3 Tests For Cross-national Invariance Of "Choice"mentioning
confidence: 99%
See 1 more Smart Citation
“…3 For partial exact invariance conditions, we considered situations in which 25%, 50%, 75%, and 100% of the compared groups were countries. However, one should keep in mind that if the focus of research is on comparisons both across countries and time points simultaneously, the number of groups may quickly increase to 90 and more (Marsh et al, 2017;Zercher et al, 2015).…”
Section: Simulation Study Conditions For Simulationsmentioning
confidence: 99%
“…Approximate measurement invariance allows small differences in loadings or intercepts across groups. Moreover, testing for approximate measurement invariance can be performed within the Bayesian SEM framework Muthén and Asparouhov 2013;van de Schoot et al 2013;Zercher et al 2015).…”
Section: Measurement Invariancementioning
confidence: 99%